British Thoracic Society community-acquired pneumonia care bundle: results of a national implementation project. Issue 3 (21st July 2015) - Lim, Wei Shen; Rodrigo, Chamira; Turner, Alice M; Welham, Sally; Calvert, James M
Abstract : In 2013, 16 UK hospital trusts participated in a quality improvement programme involving implementation of a community-acquired pneumonia (CAP) care bundle. High-level data were collected on 14 962 patients admitted with CAP; bundle implementation increased from 1% in October 2012 to 20% by September 2013. Analysis of patient-level data on 2118 adults (median age 75.3 years) found that in the bundle-implementation group, significantly more patients received antibiotics within 4 h of admission (adjusted OR 1.52, 95% CI 1.08 to 2.14, p=0.016) and 30-day inpatient mortality was lower (8.8% vs 13.6%; adjusted OR 0.59, 95% CI 0.37 to 0.95, p=0.03).